Encapsulation of nystatin in nanoliposomal formulation: characterization, stability study and antifungal activity against Candida albicans - Ebrahim Saadat; Rassoul Dinarvand; Pedram Ebrahimnejad (Mazandaran University of Medical Sciences, 2016)
In this study, nystatin liposomal formulation was prepared and characterized. The physicochemical properties of formulations including vesicle size, drug entrapment stability and in vitro release were studied. The highest entrapment efficiency of nystatin into liposomes was obtained about 70% when cholesterol (CHO) was added to the formulations prepared with dipalmitoylphosphatidylcholine. In addition, the drug entrapment efficiency was decreased when distearoylphosphatidylcholine was used   but it was improved by addition of CHO and hydration   with 9% sucrose solution. Liposomes with uniform size distribution and average size of 100 nm were produced.  Long term stability study indicated that the lyophilized liposomal nystatin was physically stable for at least 6 months at 4 °C. In vitro anti-fungal activity of liposomal nystatin was found to be more effective than free nystatin against Candida albicans.